2021
DOI: 10.1111/mcn.13190
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and experiences of employed women when combining exclusive breastfeeding and work: A qualitative study among office workers in Northern Ethiopia

Abstract: Evidence from different countries shows that the level of support given to mothers who return to paid employment can significantly determine the duration of exclusive breastfeeding (EBF). However, little is known about how returning to work impacts Ethiopian women's EBF practice. The aim of this study was to explore women's attitudes and experiences of EBF when they returned to work. Mothers who had an infant of less than 12 months, working in government institutions in Tigray region, Ethiopia, were invited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 27 publications
(44 reference statements)
0
19
0
1
Order By: Relevance
“…For instance, in Indonesia, although workplaces are mandated by law to provide lactation facilities, Wagiu Basrowi et al (25) found that companies are not held accountable when they fail to comply. In Ethiopia, Gebrekidan et al (30) reported that while women were ostensibly allowed to take breaks to breastfeed their infants, they relied on coworkers to cover their workload and could only ask for such favours a few times before colleagues would be upset.…”
Section: Workplace-based Support To Breastfeedingmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in Indonesia, although workplaces are mandated by law to provide lactation facilities, Wagiu Basrowi et al (25) found that companies are not held accountable when they fail to comply. In Ethiopia, Gebrekidan et al (30) reported that while women were ostensibly allowed to take breaks to breastfeed their infants, they relied on coworkers to cover their workload and could only ask for such favours a few times before colleagues would be upset.…”
Section: Workplace-based Support To Breastfeedingmentioning
confidence: 99%
“…In these and similar cases, supporting mothers to breastfeed or pump breastmilk requires that workplaces have routine break times that are supported and enforced by management (31), as well as a private, clean space where women feel comfortable and safe. In addition to providing material and regulatory support, employers can encourage recommended breastfeeding practices through community outreach campaigns that aim to sensitise husbands and extended family members to the challenge faced by new mothers who must balance heavy burdens of professional and domestic work in order to continue breastfeeding (30,32).…”
Section: Workplace-based Support To Breastfeedingmentioning
confidence: 99%
“…There are different studies on the breastfeeding experience of employed mothers in Ethiopia [ 11 , 12 ]. There are also studies from other countries, that focus on exploring employers’ perception and experience of employed mothers’ breastfeeding in different work environments [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Knowledge and attitudes also contribute to improve breastfeeding practices, but they need support from their husbands and coworkers as well as adequate working conditions for mothers. 12 The formula feeding practice can also inhibit exclusive breastfeeding for working women. 6 The discomfort and embarrassment in expressing breast milk at work lead many women to give formula milk or stop breastfeeding altogether.…”
Section: Introductionmentioning
confidence: 99%